Edge‐Nitrogen Enriched Porous Carbon Nanosheets Anodes with Enlarged Interlayer Distance for Fast Charging Sodium‐Ion Batteries. Issue 48 (21st October 2022) - Xu, Chong; Yang, Wang; Ma, Guang; Che, Sai; Li, Yun; Jia, Yan; Chen, Ni; Huang, Guoyong; Li, Yongfeng
Abstract: The application of nitrogen‐doped porous carbon for sodium‐ion batteries (SIBs) has attracted tremendous attention. Herein, a series of edge‐nitrogen enriched porous carbon nanosheets (ENPCNs) are synthesized by annealing g‐C3 N4 and glucose in a sealed graphite crucible at different temperatures ( T = 700, 800, and 900 °C). Surprisingly, under the closed thermal treatment condition, the ENPCNs‐T possess a high N‐doping level (>12.62 at%) and different carbon interlayer distance ranging from 0.429 to 0.487 nm. By correlating the carbon interlayer distance with the N configurations of ENPCNs‐T materials, a reasonable perception of the important influence of pyrrolic N on the increase of carbon interlayer distance is proposed. When applied as anode materials for SIBs, the ENPCNs‐800 exhibits a remarkable capacity (294.1 mAh g −1 at 0.1 A g −1 ), excellent rate performance (132.8 mAh g −1 at 10 A g −1 ), and outstanding cycle life (180.6 mAh g −1 at 1 A g −1 after 1000 cycles with a capacity retention of 104.7%). Meanwhile, the characterizations of cyclic voltammetry, galvanostatic intermittent titration technique, and electrochemical impedance spectroscopy demonstrate that the edge‐nitrogen doping and enlarged carbon interlayer distance improve the capacity and fast charging performance of ENPCNs‐800. Considering the detailed investigation of the Na + storage mechanism and excellent electrochemical performance of ENPCNs‐800, this work can pave a new avenue for the research of SIBs. Abstract : Herein, a series of edge‐nitrogen enriched porous carbon nanosheets are synthesized by annealing g‐C3 N4 and glucose in a sealed graphite crucible. Surprisingly, the multiple N incorporation, especially the pyrrolic N, are conducive to enlarge the carbon interlayer distance, promoting the Na + insertion/extraction with excellent reversibility and facilitating the fast charging performance.